PENDAMPINGAN PENGENDALIAN KUALITAS AIR SEBAGAI UPAYA PENINGKATAN MUTU PRODUKSI ICE TUBE DI UD FROZEN ICE JEMBER - Mohammad Mardiyanto; Findi Citra Kusumasari; Aulia Brilliantina; Muhammad Ihsan Alfarizi; Degita Fahmi Brillyansyah; Yulia Rachmawati (Jurnal Padamu Negeri, 2026)
The production of crystal ice cubes poses a high risk of contamination because they are consumed without prior heating; therefore, the quality of the water used as the primary raw material is a crucial factor in ensuring product safety. At the micro enterprise level, water quality control is often not carried out systematically, even when filtration systems are in use. This situation was also observed at UD Frozen Ice, Jember, where water quality management remains reactive and lacks structured procedures or monitoring systems. This community service activity aims to enhance the partner’s capacity in water quality control through a simple and practical approach to strengthening operational systems. Implementation methods include identifying initial conditions, determining critical control points for water quality, designing a control system, providing implementation support, as well as monitoring and evaluation. The developed system includes the creation of a filtration maintenance schedule, tank cleaning procedures, and the implementation of a monitoring logbook. The results of the activity demonstrate improved consistency in water quality management, marked by the implementation of a more regular maintenance schedule, periodic tank sanitation, and the use of a recording system as a monitoring tool. Additionally, the partners demonstrated improved ability to identify potential deviations in water quality. Thus, system-strengthening-based assistance proved effective in enhancing raw material quality control at the micro industry. This approach has the potential to serve as a first step toward implementing a more comprehensive and sustainable food safety system. In practice, the implementation of maintenance schedules and monitoring logbooks provides easy-to-follow operational guidelines for maintaining consistent water quality throughout the production process.